Non-oxidative methane/methanol mixture reforming over mesoporous ni-cu/al2o3 co-doped catalyst for cleaner hydrogen production - Bawadi, Abdullah; Ali, Awad; Nurliyana, Masiran; M., Abdus Salam; Vo, Dai-Viet N. (2018)
Hydrogen is often considered as a promising alternative energy carrier and clean fuel. Hence, many efforts are directed in developing efficient, economic and green approaches for hydrogen production. Thermo catalytic decomposition over Ni supported catalyst has gained abundant interest in producing hydrogen and elemental carbon by non-oxidative decomposition of various hydrocarbons and their mixtures [1]. The aim of this presented research work it to develop highly efficient and stable promoted catalyst and to explore their activity towards methane/methanol mixture decomposition. This research is based on the profound analysis of published work, which allows selection of appropriate methods and material for this research. 50%Ni/Al2O3 and 50%Ni- 15%Cu/Al2O3 were synthesized by wet impregnation method and after that the interfacial properties of the catalyst were studied by employing various analytical techniques [2]. The stoichiometric amounts of Ni (NO3)2.6H2O, Cu (NO3)2.3H2O and -Al2O3 were used in this research study. Furthermore, N2 as an inert gas, H2 as activation gas and 2%CH3OH/CH4 was employed as feedstock for thermo catalytic decomposition reaction.